(untitled) (KYAMC Journal, 2017)
Two pregnant women with around 33-34 weeks of gestation were reported to Gynaecology and Obstetrics OPD of North Bengal Medical College Hospital, Bangladesh for last trimester antenatal checkup. They were primigravida with around 23-25 years of ages without previous antenatal check up. Both of them had normal course of pregnancy. Ultrasounds of pregnancy profile were done. It was observed in first case that septum pellucidum was absent in brain with partially formed falx cerebri, interhemispheric fissure. Occipital horn was rudimentary and thalami and basal ganglia were partially separated. This case was diagnosed as a case of semi lobar holoprocencephaly. In another case, septum pellucidum, falx cerebri and interhemispheric fissure were absent. Ventricle was monoventricular in appearance and thalami were fused. This case was diagnosed as a case of alobar holoprosencephaly. The importances of these classical cases of alobar and semi lobar holoprosencephalies are to make aware the radiologists to the imaging manifestations of holoprosencephalies and come to early diagnosis. If these cases are being diagnosed at an early stage of pregnancy, medical termination of pregnancy can be performed and maternal psychological trauma of bearing a deformed fetus can be avoided. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 64-68